Ergonomic intervention program of computer workstation for school community during Covid-19 pandemic / Muhammad Azri Syafiq Mohamed Ariff - Muhammad Azri Syafiq, Mohamed Ariff (2022)
During the pandemic, there have been multiple reports from the education sector that home schooling is not practical. This is worrying because the pandemic is expected not to end within a short of period of time. Thus, this study was undertaken to observe the ergonomics of teachers' and students' home computer workstations while home schooling and tutoring. By doing a three-part survey questionnaire on ergonomics practices on home computer workstation was sent toward respondents through social media platform. The respondents involved employees from education sector and also students ranging from primary to secondary schools, who were forced to adapt into home schooling session due to the COVID-19 pandemic. The data is collected in the form of musculoskeletal disease symptoms and also computer vision syndrome symptoms. From there, it is then analyzed to identify incorrect postures and discomfort level faced by the subjects. An ergonomic intervention program is introduced as a part of the questionnaire and subjects are required to give their opinion on the program. The results obtained showed that there is indeed a symptom such as back aches and dry eyes which may develop into musculoskeletal disease and computer vision syndrome. The ergonomic intervention introduced received a good review from the subjects.